The influence of responsible leadership on teachers’ green behavior: The mediating role of psychological capital - Wang, Xinyi; Kou, Fengtian; Zhu, Kexuan (Frontiers in Psychology, 2023)
This research aimed to explore the impact of responsible leadership on teachers’ green behavior in Chinese university, and applied psychological capital as a mediator variable to establish a research model. A questionnaire was conducted with 303 teachers using convenience sampling. The results show that responsible leadership has a positive yet significant effect on teachers’ green behavior. It also shows positive impact on psychological capital. Furthermore, psychological capital is shown to positively impact teachers’ green behavior, while having a mediating effect between responsible leadership and teachers’ green behavior.